PENGARUH TINGKAT PENDIDIKAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA BADAN PUSAT STATISTIK KABUPATEN BARRU - Amaliah, Reski Nur (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
Some individuals who are assessed at the level of education are inadequate to the job and are also reviewed in the culture that is within the organization the typical thing is the dominant culture and the other culture disappears slowly, usually when one is dominant and the other has no power. The study aims to see how the organizational level of education and culture affects the performance of employees on Barru Central Bureau Statistics. The data-collection techniques used in this study are questionnaires, observations, and library studies. The sample in this study Numbers 21. Data analysis techniques in this study use computerized system analysis techniques (SPSS version 21). Partial research at the level of education (x1) affects positive and insignificant performance (Y). Partially the organizational culture (X2) has a positive and significant impact on an employee's performance (Y).